(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The subject of human rights is not new. It has been ingrained in the societies from time immemorial. This topic has assumed a great importance in the contemporary world due to the result of gross violations of these rights. Human rights are the rights which are essential for leading a good normal and dignified life as a human being. Human rights can be generally defined as those rights, which are inherent in our nature and without which we cannot live as human beings. Human rights and fundamental freedoms allow us to fully develop and use our human qualities, our intelligence and other needs. Human rights are sometimes also called fundamentals rights or basic rights or even natural rights. Another way to describe them would be to call them "common rights" for they are the rights, which all men and women in the world should share. These are inalienable rights of all members of human family. Human rights means the rights relating to life, liberty, equality and dignity of the individual guaranteed by the Constitution or embodied in the international covenants and enforceable by courts in India.4 These are those minimum rights, which every individual must have against the state or other public authority by virtue of his being a human being.5 As a matter of fact, human rights can be termed as universal and politically identified human values. The contemporary conception of human rights, though rooted in the rich heritage of past, is of recent origin and was reflected for the first time in the Charter of the United Nations which was adopted in 1945.